Iterative Based Time Domain Equalization Method for DFTS-OFD in Highly Mobile Environments - Pongsathorn Reangsuntea; Arttapol Reangsuntea; Pisit Boonsrimuang; Kazuo Mori; Hideo Kobayashi (My University, 1970)
In highly mobile environments, signal quality of discrete Fourier transform spreading-orthogonal frequency division multiplexing (DFTS-OFDM) with a frequency domain equalization method would be degraded due to the occurrence of inter-channel interference (ICI). To solve this problem, this paper proposes an iterative based time domain equalization (TDE) method with a time domain channel impulse response (CIR) estimation for DFTS-OFDM signals. The salient features of the proposed method are the use of a time domain training sequence (TS) in the estimation of CIR instead the conventional pilot subcarriers and to employ the TDE method with a maximum likelihood (ML) estimation instead of the conventional one-tap minimum mean square error frequency domain equalization (One-Tap MMSE- FDE) method. This paper also proposes a low complexity iterative based TDE method using the properties of a symmetric banded CIR transfer matrix for solving the simultaneous equations instead of direct calculation of an inverse matrix. It also presents various simulation results in highly mobile environments to demonstrate the effectiveness of the proposed iterative based TDE with CIR estimation for the TS inserted DFTS-OFDM signals compared to the conventional One-Tap MMSE-FDE method.
Keywords: PAPR reduction in OFDM